The epistemics of presupposition - Gillies, Anthony S. (Proceedings of the Amsterdam Colloquium, 1999)
Successful linguistic interaction requires agents to agents to be able to reason about what is being said. Given this, it is natural to pursue the extent to which general epistemic principles can be brought to bear on semantic phenomena. In particular, I look at the interaction between the dynamics of belief and presupposition. A simple defeasible update semantics for presupposition is given in which accommodation is understood as belief updating, and presupposition failure as failed belief revision.